2017
DOI: 10.1177/0972063416682563
|View full text |Cite
|
Sign up to set email alerts
|

A Holistic Framework for Conceptualizing Hospital Service Quality

Abstract: Managing service quality has always been one of the most important areas of concern in hospitals. With the advancement of lifestyle, education and awareness among consumers, they are becoming more and more demanding. This is the reason why hospitals are spending huge amount in managing service quality that leads to satisfaction among patients and ultimately contributes in brand building. Thus the first and most important consideration is to determine and understand the various dimensions of service quality in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 19 publications
0
13
0
1
Order By: Relevance
“…The study found that there were gaps in all the dimensions and that the gaps were statistically significant, with values ⩽0.05. Swain and Kar (2017) developed a conceptual framework of hospital SQ by identifying 15 different dimensions, and these dimensions are further clubbed under 3 broad dimensions of infrastructural, procedural and interactional dimensions. The summary of the literature review is contained in Table II to show the research gap that necessitated this study.…”
Section: Service Quality Dimensions and Attributesmentioning
confidence: 99%
“…The study found that there were gaps in all the dimensions and that the gaps were statistically significant, with values ⩽0.05. Swain and Kar (2017) developed a conceptual framework of hospital SQ by identifying 15 different dimensions, and these dimensions are further clubbed under 3 broad dimensions of infrastructural, procedural and interactional dimensions. The summary of the literature review is contained in Table II to show the research gap that necessitated this study.…”
Section: Service Quality Dimensions and Attributesmentioning
confidence: 99%
“…To determine and evaluate patient satisfaction we need to study the functional and technical aspects of personnel quality in hospitals (Kane et al, 1997).In the Indian context, several researchers such as (Padma et al, 2010 andSwain andKar, 2017;and Duggirala et al 2008) used personnel quality aspects as an influential factor on patient satisfaction when they measured the healthcare service quality. In such a way, four significant dimensions of personnel quality namely; doctors' quality, nurses' quality, administrative staff quality and interpreters' quality represent the human aspects of delivering service quality which contributes to the success and sustainability of the business.…”
Section: Personnel-quality Dimensionsmentioning
confidence: 99%
“…In healthcare sectors, personnel quality represents as an understanding and meeting the needs of patients concerning types of healthcare and other services delivered by the management staff, doctors, nurses, and interpreters in hospitals. It is expected to greatly contribute to the success and sustained growth of the health care business (Kitapci et al, 2014;Padma et al, 2009Padma et al, , 2010Swain andKar, 2017 andDuggirala et al, 2008). Indian healthcare sector is a fast growing industry with a high level of demand for services from native as well as foreign patients.…”
Section: Introductionmentioning
confidence: 99%
“…The hospital should understand and manage well different dimensions: infrastructure, resource availability, waiting time, food, clinical procedures, administrative procedures, price, trustworthiness, information availability, patient safety, continuity, personalized attention, and staff attitude, quality of outcome and religions needs. All these dimensions can be used for measuring service quality management in both private and public hospitals (Swain & Kar, 2017). Clients will share positive experience that satisfied by hospital services, if not satisfied and any complain about services, the hospital can correct the drawbacks.…”
Section: Introductionmentioning
confidence: 99%